Electron paramagnetic resonance studies of artificial supramolecular structures and biological systems - Tait, C (2015)
The research described in this thesis employs a variety of Electron Paramagnetic Resonance (EPR) techniques for the study of the electronic and structural properties of artificial supramolecular porphyrin systems and of protein complexes of biological relevance. The electron delocalisation in the cationic radical and photoexcited triplet states of linear and cyclic Π-conjugated multiporphyrin arrays was investigated. In the radical cations, information on the extent of delocalisation can be inferred from the measurement of hyperfine couplings, either indirectly from the continuous wave EPR spectrum or directly using pulsed hyperfine EPR techniques. The results of room temperature EPR experiments showed complete delocalisation of the electron on the timescale of the EPR experiments, but frozen solution EPR measurements revealed localisation onto mainly two to three porphyrin units in the larger porphyrin systems. Information on the delocalisation of the triplet state in the same porphyrin systems is contained both in the hyperfine couplings and in the zero-field splitting (ZFS) interaction. The results outlined in this thesis show that the hyperfine couplings provide a much more accurate estimate of the extent of delocalisation. The trends in proton and nitrogen hyperfine couplings with the size of the porphyrin systems indicate uneven spin density distributions over the linear arrays, but complete delocalisation in the cyclic systems. Time-resolved EPR and magnetophotoselection experiments have shown a reorientation of the zero-field splitting tensor between a single porphyrin unit and longer linear arrays, resulting in alignment of the main optical transition moment and the Z axis of the ZFS tensor. Continuous wave and pulsed dipolar EPR techniques were employed for the determination of the structure of two different protein complexes, the homomultimeric twin-arginine translocase A (TatA) protein channel and the ferredoxin-P450 complex of the electron transport chain in Novosphingobium aromaticivorans. The interaction between nitroxide spin labels introduced at different positions of the TatA monomer was investigated in the complex reconstituted in detergent micelles by analysing the dipolar broadening of the EPR spectra and the results of three- and four-pulse Double Electron-Electron Resonance (DEER) measurements. In combination with results from NMR and molecular dynamics calculations, a structure for the channel complex was proposed. The structure of the ferredoxin-cytochrome P450 complex was investigated by orientation-selective DEER between nitroxide labels introduced on the cytochrome P450 protein and the iron-sulfur cluster of the ferredoxin. The distance and orientation information contained in the experimental DEER data was interpreted in terms of a structural model of the protein complex by orientation-selective DEER simulations combined with a modelling approach based on protein-protein docking.